Loadings in Thermal Barrier Coatings of Jet Engine Turbine Blades An Experimental Research and Numerical Modeling - Sadowski, Tomasz; Golewski, Przemysław (SpringerBriefs in Computational Mechanics, 2016)
This book discusses complex loadings of turbine blades and protective layer Thermal Barrier Coating (TBC), under real working airplane jet conditions. They obey both multi-axial mechanical loading and sudden temperature variation during starting and landing of the airplanes. In particular, two types of blades are analyzed: stationary and rotating, which are widely applied in turbine engines produced by airplane factories.